Concepções de educação ambiental dos professores do município de Canapi/AL - Ventura, Juliana Santos da Silva (2021)
This dissertation approaching is about the Environmental Education (EE) in the school context of the city of Canapi/AL, havingas the general goal the understanding of the conceptions of EE of teachers in the municipal education network, taking into account the local reality and the challenges that surrounds the public school. The present study was developed as an investigation of a qualitative nature that is looking foward to understand the work and perspective of educators on EE. Thus, this is a case study developed at the Presidente Tancredo de Almeida Neves Municipal School of Basic Education, whose sample is composed of 12 teaching participants who work in the final years of Elementary School (from 6th to 9th grade), using as data collection instruments, a questionnaire, guiding documents on education and the work carried out by the school (National Common Curriculum Base – BNCC, Curriculum Reference of the State of Alagoas, School Regiment and Political-Pedagogical Project – PPP) and semi-structured interview. Data analysis was performed using the content analysis technique from the perspective of Bardin (2011). The relevance of this study stems from the fact that, in recent decades, EE, which is an essential element of education and must be worked on both formally and informally, has proved to be an important path in facing the current environmental and in the adequacy of the relationship between human beings and nature, assuming the commitment to promote changes in values, behavior and attitudes in order to build a fairer and more environmentally sustainable society. The results obtained showed that the conceptions of the environment and EE of the researched professors follow a naturalist, conservationist and pragmatic bias and reverberate in the way these professors describe their pedagogical practices, which are aimed at raising awareness about conservation and environmental preservation. The difficulty in locating EE in the curriculum and in the context of different subjects was also observed. The study came to the conclusion that the initial and continuing education received by teachers does not prepare them sufficiently to address social and environmental issues and that, for the emergence of a Critical EE, it is necessary that teacher education addresses this field of knowledge in a way interdisciplinary and bring teaching closer to the discoveries and advances of scientific research.